The Potential of Vā Part 2: Theoretical Frameworks of the Vā - Simati-Kumar, Benita (Te Kaharoa, 2021)
The article presented is part of a series of articles that composed an exegesis, submitted in fulfilment of the requirements for the degree of Doctor of Philosophy. The series is a narrative of discovery through practice-led research. Each article reveals its purpose and significance that leads into the next series, which then eventuate to that final design proposal.The exegesis is presented in this format, to break down the components that assisted in practice-led research. Each article can be read and unpacked on its own as a learning tool. The purpose of this edited series is for the exegesis to be more accessible and adaptable creatively to those being introduced to practice-led research.